Peningkatan Prestasi Belajar Matematika dengan Menggunakan Metode Pembelajaran Kooperatif Tipe TGT (Team Games Tournament) Pada Siswa Kelas VII Negeri 4 Siborongborong - Hutagalung, S Lumumba (CV. Creative Tugu Pena, 2020)
The purpose of this article was to determine the effect of cooperative learning TGT (Team Games Tournament) in learning outcomes of Mathematics material numbers for the seventh grade students of State of Junior High School (SMPN) 4 Siborongborong, to find out how the high students’ learning achievement by applying TGT type cooperative learning method. This research used classroom action research as much as three cycles. Each round consists of four stages, namely design, activity and observation, reflection, and refinement. The targets of this research were students of class VII SMPN 4 Siborongborong, Siborongborong District. The data obtained in the form of formative test results, observation sheets of teaching and learning activities. The result found that the student achievement increased from cycle I up to cycle III namely, cycle I (66.67%), cycle II (79.17%), cycle III (91.67%). The conclusion of this study was the cooperative method of the TGT model have a positive effect on student achievement in class VII SMPN 4 Siborongborong and it’s learning model can be used as an alternative to mathematics learning. Keywords: Cooperative Method, TGT (Team Games Tournament), Students’ Learning Achievement